A representação da Universidade Federal do Rio Grande do Norte nos conselhos gestores municipais: uma análise a partir da perspectiva das teorias democráticas - Valentim, Maria do Socorro (2016)
This paper discusses the UFRN participation in the Councils Municipal Managers of Social Policies through a case study of its representation in the Municipal Board of Education in Natal / RN, as the democratic participatory system assumption adopted by the Federal Constitution of 1988. The descriptive search, as a transversal character, with data collection gathered in the Council and by semi-structured interviews with representatives of the UFRN Education Center, as well with the effective members of CME, will have a qualitative approach to analyze the obtained content. Therefore, we start understanding that throughout history democracy has become the political system best suited to the social organization, protection of individual rights and freedoms and that popular sovereignty has established itself as the foundation for its legitimacy. In this respect, social participation is presented as one of the most important tools of democracy and true expression of popular sovereignty. Therefore, it opens up space for research of democratic aspects involved in the representation of UFRN close to the Councils, providing opportunities to check its role in this context, the contribution of possibilities to the country's democratization process. The emergence of social policies management councils reveals the strength of citizen participation in the intervention and the formulation of public policies, in order to increase their efficiency through social control. Therefore, this study focused on democratic theories to analyze how they can contribute to the improvement of management councils, as well as the role of the Academy in this regard. A certain influence of the Municipal Executive was detected in the activities of the Council, limiting the autonomy of its activities and the amplitude of the scope of the deliberations initiated there. About the UFRN's chair at the CME in Natal, it does not constitute a full and wide representation of the Institution, it is confined to the Education Center and is compromised at a time when there are no discussions at the University about its positioning on the issues to be addressed Deliberated in that instance. It is concluded that it is necessary to emphasize social representations in the management councils and better conditions for broad participation of the members of the University in these spaces, aiming to reach real possibilities of contribution and effective exercise of public deliberation.